PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING DAN TALKING STICK TERHADAP HASIL BELAJAR IPS PADA PESERTA DIDIK SEKOLAH DASAR DI KECAMATAN DEMAK - Masrokhah Masrokhah; Sri Utaminingsih; Su`ad Su`ad (Universitas Muria Kudus, 2021)
The purpose of research it is to determine : (1) the effect of the application of the model study of quantum against the results of learning Theme 5 on the charge lesson IPS participants learners grade elementary school in the District of Demak , (2) the effect of the application of the model of learning talking stick to the result of learning Scene 5 in charge of the lesson IPS participants learners grade elementary school in the District of Demak, and (3) differences in the influence of the model of learning quantum teaching and talking stick to the result of learning Theme 5 on the charge lesson IPS participants learners grade elementary school in the District of Demak. The method of research using a quasi-experimental design , with the population of the entire student class V School Elementary District of Demak from 55 elementary schools with the number of 1,627 participants learners . The sample of the study is the participant students grade VA SD Bintoro 5 (35 participant students ) and a class VB SD Bintoro 5 (34 participant students ), as a class experiment . As a class control is student class V SD Bintoro 2 with the number of 41 participants learners.